Pemanfaatan Media YouTube dan Blog Pembelajaran Materi Statistika dan Hubungannya dengan Kemampuan Pemecahan Masalah Matematis dan Prestasi Belajar - Yovita Vera Christina; Samuel Lukas (Syntax Corporation Indonesia, 2024)
This research aims to examine the use of learning media that is good, effective and appropriate to the needs and characteristics of students through YouTube media and Learning Blogs and its relationship with mathematical problemsolving abilities and learning achievement. The method used was quantitative quasi-experiment with correlation tests on mathematical problem solving abilities and learning achievement for classes VIII C and VIII D at SMP Tarakanita 2 Jakarta with 58 respondents. The Cronbach's Alpha test on the YouTube media test instruments (0.83), Blog (0.82), Problem Solving (Pretest 0.92 and Posttest 0.86), and Achievement (0.90) shows high validity and reliability. Based on non-parametric hypothesis testing using the Spearman Test method, it is known that there is a correlation between the use of YouTube media and Problem Solving (R-count 0.37), YouTube and Achievement (R-count 0.41), Blogs and Problem Solving (R-count 0. .42), and Blog with Achievement (R-count .39). The non-parametric Mann Whitney test in the control class and experimental class regarding achievement was stated to be identical with the same mean and variance so that there was no difference in the increase in NGain in the two classes.